2014
DOI: 10.1007/s11845-014-1104-5
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance for low-risk prostate cancer: diversity of practice across Europe

Abstract: Urologists not adhering to an AS protocol or participating in a clinical trial appear to apply less rigorous criteria for both eligibility and monitoring in AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Currently, the physician’s recommendation has the biggest influence on a patient’s decision to select AS [ 4 , 8 , 12 ]. Variation in AS management is frequently attributed to the physician’s perspectives, practice patterns, or abilities to effectively communicate the merits of AS [ 13 ]. Despite their influential role, physicians receive little to no training in counseling patients on AS [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the physician’s recommendation has the biggest influence on a patient’s decision to select AS [ 4 , 8 , 12 ]. Variation in AS management is frequently attributed to the physician’s perspectives, practice patterns, or abilities to effectively communicate the merits of AS [ 13 ]. Despite their influential role, physicians receive little to no training in counseling patients on AS [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings of a study conducted by Azmi et al 34 in 2013 showed that a relatively high level of agreement exists between the conclusions of various studies of AS that patients with serum PSA levels ≤10 ng/ml and a biopsy sample Gleason score of ≤3+3 = 6 are appropriate for AS, although, clearly less agreement exists in terms of the most appropriate clinical tumour stage, number of tumour-positive biopsy core samples and patient age 34 . Furthermore, little consensus exists in the literature regarding how to optimally assess progression of localized prostate cancer; although, the majority of studies used serial measurements of serum PSA levels and DRE, with some also adding prostate biopsy sampling 34 . No consensus has been reached regarding the frequency of repeat investigations or on the most appropriate triggers for initiation of radical treatment across the various AS programmes 34 .…”
Section: [H2] Increase In Tumour Volumementioning
confidence: 99%
“…Furthermore, little consensus exists in the literature regarding how to optimally assess progression of localized prostate cancer; although, the majority of studies used serial measurements of serum PSA levels and DRE, with some also adding prostate biopsy sampling 34 . No consensus has been reached regarding the frequency of repeat investigations or on the most appropriate triggers for initiation of radical treatment across the various AS programmes 34 . To enable truly evidencebased guidelines to be issued, further research that combines existing evidence whilst also gathering information from more long-term studies is needed.…”
Section: [H2] Increase In Tumour Volumementioning
confidence: 99%
“…7 8 Furthermore, a large diversity of practice across Europe has recently been reported, showing that urologists who are not participating in a clinical trial appear to apply less rigorous criteria for both inclusion and follow-up (FU). 9 In 1999, we began a prospective AS clinical trial in our average-sized clinic with the intention of assessing the outcome of patients with PCa managed with AS. We hoped this study would provide insight into a real-world application of AS in a smaller non-academic hospital in the European setting.…”
Section: Introductionmentioning
confidence: 99%